Towards autonomous creation of service chains on cloud markets. (9th August 2019) - Pittl, Benedikt; Ul-Haq, Irfan; Mach, Werner; Schikuta, Erich
Today, cloud services, such as virtual machines, are traded directly at fixed prices between consumers and providers on platforms, e.g. Amazon EC2. The recent development of Amazon's EC2 spot market shows that dynamic cloud markets are gaining popularity. Hence, autonomous multi-round bilateral negotiations, also known as bazaar negotiations, are a promising approach for trading cloud services on future cloud markets. They play a vital role for composing service chains. Based on a formal description we describe such service chains and derive different negotiation types. We implement them in a simulation environment and evaluate our approach by executing different market scenarios. Therefore, we developed three negotiation strategies for cloud resellers. Our simulation results show that cloud resellers as well as their negotiation strategies have a significant impact on the resource allocation of cloud markets. Very high as well as very low mark-ups reduce the profit of a reseller.